New Caridina (Atyidae - Crustacea) shrimps collected from Hai Van mountain pass (Thua Thien - Hue province) - Tu, Do Van; Thanh, Dang Ngoc (Academia Journal of Biology, 2012)
﻿For the first time, Caridina (Atyidae - Crustacea) shrimps has been collected from streams highgly located in Hai Van Mountain Pass, between Thua Thien - Hue and Da Nang provinces, central Vietnam. Among them, two species are described as new for science: Caridina haivanensis sp. nov. and Caridina pseudoflavilineatasp. nov.1. Caridina haivanensis sp. nov.Rostrum short, approximately reaching the end of the 1st antennular peduncule segment,. The dorsal border bearing frequently 0-3 teeth, the ventral havng no teeth or only 1. No teeth on the carapace. Endopod I of the male kidney- shaped, distal appendix overeaching its extremity. Endopod II with stout finger ﻿shaped, appendix masculina extending beyond the middle of Endopod II. Appendix interna not reaching the middle of appendix masculina. Telso acutely ending. Big eggs, dimensions : 1.1 - 1.3 · 0.75 - 0.8 m/m.2. Caridina pseudoflavilineata sp. nov.Shrimp of small size. Rostrum lanceolate in form reaching the end of the 2nd or 3rd antennular peduncule segment. The dorsal border bearing 9-12 teeth, with 3-4 teeth on the carapace. The ventral border with 3-4 teeth. Endopod I of the male coniform, distal appendix overeaching its extremity. Endopod II with fingerform,appendix masculina extending beyond the middle of Endopod II. Appendix interna short. Eggs dimensions: 1.1 · 0.75 m/m.